1996
DOI: 10.1002/(sici)1096-9071(199609)50:1<97::aid-jmv16>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence studies of GB Virus-C infection using reverse transcriptase-polymerase chain reaction

Abstract: Among the three recently described GB viruses (GBV-A, GBV-B, and GBV-C), only GBV-C has been linked to cryptogenic hepatitis in man. Because of the limited utility of currently available research tests to determine antibody response to GBV-C proteins, the prevalence of GBV-C RNA in human sera was studied using reverse transcription-polymerase chain reaction (RT-PCR). The prevalence of GBV-C is higher among volunteer blood donors with elevated serum alanine aminotransferase (ALT) levels (3.9%) than among volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
126
2
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(138 citation statements)
references
References 29 publications
9
126
2
1
Order By: Relevance
“…12 We found no significant correlation between GBV-C/HGV infection and age or sex. This is consistent with some 38 but not all 27 previous reports. We evaluated GBV-C/HGV infection in pregnant women from urban and semi-rural areas of Gabon and found no significant difference between these two areas.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…12 We found no significant correlation between GBV-C/HGV infection and age or sex. This is consistent with some 38 but not all 27 previous reports. We evaluated GBV-C/HGV infection in pregnant women from urban and semi-rural areas of Gabon and found no significant difference between these two areas.…”
Section: Discussionsupporting
confidence: 92%
“…ers) 32,33 in the Gabonese population. The prevalence of GBV-C/HGV in Gabon is similar to that reported in Ghana, 27 South Africa 28,29 and central Africa. 12 We found no significant correlation between GBV-C/HGV infection and age or sex.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The natural history of GBV-C/HGV infection is at present not fully understood and its potential to cause hepatitis in humans is questionable. Epidemiological studies have indicated that it does not cause acute or chronic hepatitis [1][2][3][4]. In recent years numerous studies have been published in which coinfection with GBV-C/HGV and the human immunodeficiency virus (HIV) have been associated with slower progression of the illness and a higher survival rate of patients once AIDS has developed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Infection is common in the normal population with up to 12.9% prevalence among paid blood donors in the USA [Dawson et al, 1996], 11%-14% in West Africa or South Africa [Dawson et al, 1996;Casteling et al, 1998], and as high as 37% among HIV-infected individuals [Tillmann and Manns, 2001]. GBV-C has been classified tentatively as a member of the Flaviviridae family due to similarities in genome organization and genetic relatedness [Leary et al, 1996a].…”
Section: Introductionmentioning
confidence: 99%